Interleaved quadratic boost converter integrated with Dickson voltage multiplier with energy storage for high power photo voltaic applications - Dhanaraj Amudhavalli; Nalin Kant Mohanty; Ashwin Kumar Sahoo (Institute of Advanced Engineering and Science, 2021)
In this paper interleaved quadratic boost converter with Dickson voltage multiplier is proposed. Photovoltaic system is connected to high power load through the proposed converter. Structure of this high gain interleaved converter comprised of two stages: interleaved quadratic boost converter stage and Dickson voltage multiplier stage. Interleaved quadratic boost converter is a parallel combination of two quadratic boost converter. The interleaving increases frequency of converter that could be filtered using small capacitors, making input current smoother than the current of conventional quadratic boost converter. Thus, interleaved circuit minimizes current ripple present in input current, cascading of voltage multiplier cell increases the gain voltage ratio of converter making it suitable for high power, high voltage gain photo voltaic applications. Stress voltage of the switches and reverse recovery problems gets reduced, thereby reducing EMI problems. 300W prototype capable of increasing 24V input voltage to 400V output voltage is designed and results tested using MATLAB/Simulink software. Hardware prototype is also implemented to verify simulation results. Also, application of this converter in integrated energy storage is demonstrated.